PEMETAAN, PEMAHAMAN, PENGGUNAAN MODEL INQUIRI KOLABORATIF PADA PEMBELAJARAN IPA: DIPANDANG DARI ASPEK GURU DAN SISWA - Mery Berlian; Habibul Hakim; Rian Vebrianto (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
The purpose of this study is to ascertain how instructors and students at SDN 017 Bukit Payung plan, understand, and apply the collaborative inquiry learning approach in scientific instruction. The study included a case study and a qualitative methodology. Fifth-grade instructors and students who were actively engaged in scientific education made up the research subjects. Techniques for gathering data included recordkeeping, interviews, and observation. The phases of data reduction, data presentation, and conclusion drawing were used to examine the data. Source triangulation and procedure triangulation were used to attain data validity. Because the majority of learning phases were carried out as best they could, the findings demonstrated that the mapping of the collaborative inquiry model's execution fell into the